Thwarted belongingness, perceived burdensomeness, and acquired capability for suicide among university students of Bangladesh: Scales validation and status assessment - Arafat, S. M. Yasir; Hussain, Fahad; Zaman, Mir Susmita; Tabassum, Tamanna; Islam, Md. Khayrul; Shormi, Farzana Rabin; Khan, Anisur Rahman; Islam, Md. Rabiul; Redwan, A. S. M.; Giasuddin, Noor Ahmed; Mubashir, Anila; Khan, Md. Abdullah Saeed (Frontiers in Psychiatry, 2022)
Background: Identification of prior mental events of suicide attempts has immense importance in suicide prevention. However, it has not been studied in Bangladesh as there was no available psychometrically valid instrument measuring it. Objectives: We aimed to test the psychometric properties of the interpersonal needs questionnaire (INQ-15) & acquired capability for suicide scale-fearlessness about death (ACSS-FAD) in Bangla along with the determination of the level of thwarted belongingness, perceived burdensomeness, and acquired capability for suicide. Methods: We collected data between 29 March and 14 April 2022 from 1207 students of medical colleges and universities in Bangladesh by Google form. We assessed the psychometric properties of Bangla INQ and ACSS-FAD scales and examined factors associated with thwarted belongingness, perceived burdensomeness, and acquired capability for suicide. Results: The mean age of the participants was 22.82±1.68 (range 18-29) years, 51% were females, 84% were graduate students, and 92% were unmarried. Both of the scales revealed acceptable levels of reliability. Confirmatory factor analysis revealed a two-factor structure of Bangla INQ after dropping three items from thwarted belongingness domain (item 9, 11, and 12) and a single factor structure for Bangla ACSS-FAD after dropping three items (item 1, 4, and 6). Perceived burdensomeness was significantly higher in females, students with a history of mental illness, family history of suicide, and the history of suicidal attempts. Fearlessness about death was significantly higher among females, non-Muslim participants, and history of suicidal attempts. Conclusions: The current study revealed psychometric properties of two suicide scales (INQ and ACSS-FAD) in Bangla that can be used in subsequent studies. The final Bangla INQ consists of twelve items into two domains having six items in each and the final Bangla ACSS-FAD consists of four items with a unidimensional structure.